Pengembangan Instrumen Pengetahuan Meows Berbasis Pemodelan Rasch - Dwi Pangesti, Wilis; Rahayu Sakti, Ina; Ratna Kusuma, Inggar; Dewi, Sawitri; Naftuhah Riani, Evicenna; Kusumawati, Anis; Nur Fitriana, Siskanita; Oetami, Soeri (2024)
The Modified Early Obstetric Warning Score (MEOWS) is a monitoring tool intended to detect early high-risk obstetric patients. MEOWS can be employed in pregnant and postpartum women to help identify, treat, and refer patients to changes in parameters that are leading to worsening. This research aimed to develop the MEOWS instrument as a warning tool for maternity cases at Banyumas Hospital. The research method utilized the validity test of the RASCH method and the reliability test of Cronbach's alpha. The results revealed that out of 20 question items, 17 were valid with ZSTD values ranging from -0.2 to 2.0, and 3 were invalid. The item reliability value was 0.93, and the result was a Cronbach's alpha value of 0.64. The sub-theme of this knowledge questionnaire comprised the urgency of using MEOWS for obstetric complications, the time of implementation of detection using MEOWS, indicators, patient identification results with scoring, scoring categories, and follow-up of scoring identification results. Conclusion: Through the development of the MEOWS instrument using indicators of patients' vital signs, it is hoped that the progression of the patient's prognosis will be better monitored.